How to Treat Diastasis Recti Abdominis with Physical Therapy: A Case Report - Gitta, S; Magyar, Z; Tardi, P; Füge, I; Járomi, M; Ács, P; Garai, J; Bódis, J; Hock, M (Journal of Diseases, 2016)
An increased inter-recti distance is a common problem in late pregnancy and during postpartum period. According to researches diastasis recti abdominis’ occurs in 35-60% of the cases. There are only assumptions about the risk factors, treatment and consequences. The aim of this study was to determine the effect of the treatment in the postpartum period using a single case study. A 33-year-old woman, six weeks after her first delivery, was recruited to the research. She complained about abdominal muscle weakness and low back pain. The patient got a three-months-long physical therapy in which the strengthening of the transverse abdominal muscles was primary. After the intervention the pathological inter-recti distance achieved the normal range almost at each reference point. This study found that the inter-recti distance was reduced when isometric contraction of the transverse abdominal muscle was performed. This suggests that this type of exercise could be effective in treating the postpartum diastasis recti and preventing the possible sequelae.